SISTEM PENDUKUNG KEPUTUSAN PREDIKSI JUMLAH PENUMPANG UNTUK EVALUASI KAPASITAS HALTE BUS TRANS JOGJA DENGAN METODE EXPONENTIAL SMOOTHING DAN LEAST SQUARE - Prasetiyo, Dwi; Honggowibowo, Anton Setiawan; Indrianingsih, Yuliani (Compiler, 2013)
The increasing number o f passengers Trans Jogja bus stops can result in the existing capacity can not accommodate the number of passengers comfortably. Problems that often arise include delays resulting bus passenger waiting time is longer and there is a buildup of the number of passengers at stops. As a result of these problems, the capacity o f passenger stops can be full so that prospective passengers waiting outside the bus stop. Forecasting is one very important element in the decision. In this study using stationary and trend forecasting the data because the data are not significant changes between time and swell in certain periods and a normal in periods others. Time series methods for forecasting the number o f passengers on the Trans Jogja stop using exponential smoothing calculation and least square. From these calculations the value sought MAD (Mean Absolute Deviation) or least square error is exponential smoothing and forecasting results with small error. Forecasting will be better if it contains fewer possible errors.